WhatsApp Chatbot Implementation of New Student Admission Information Service in Universitas Nahdlatul Ulama Sidoarjo - Bilqis Brillyana Citra Zoraya; Syahri, Syahri Mumin; Awang, Awang Andhyka (Universitas Islam Malang, 2025)
Universitas Nahdlatul Ulama Sidoarjo (UNUSIDA) is experiencing obstacles in providing fast and efficient new student admission information services. The high volume of inquiries, limited human resources, and the need for instant response are the main challenges. This research aims to implement whatsapp chatbot technology to improve services at the University of Nahdlatul Ulama Sidoarjo. Using the Agile method, chatbot development is carried out iteratively and incrementally to ensure that the resulting solution meets user needs. The method used in this research includes the development of a chatbot system using a suitable programming platform, followed by testing the functionality and effectiveness in providing information. The test results show that the whatsapp chatbot is able to provide accurate and relevant responses in an average time of 3 seconds. Prior to the implementation of the chatbot, the response time to prospective student questions ranged from 15-30 minutes. The implementation of whatsapp chatbot significantly improves the efficiency of information services, reduces the workload of PMB staff and increases prospective student satisfaction. This research proves the effectiveness of chatbots in improving the quality of UNUSIDA PMB information services. This research serves as an example for other institutions in utilizing chatbot technology to improve public services effectively and make a significant contribution to the development of service technology in higher education.